Audit of advertised housing and support vacancies for people with disabilities in Australia. Issue 1 (26th June 2020) - Callaway, Libby; Tregloan, Kate; Moore, Lewis; Bould, Em
Abstract: The introduction of Australia's National Disability Insurance Scheme (NDIS) has changed the way housing and support are delivered to Scheme participants. NDIS policy reform focuses on coordinated housing and support responses. These responses are guided by the Specialist Disability Accommodation (SDA) Rule, Framework and pricing and Supported Independent Living payments. To date, the National Disability Insurance Agency (NDIA) has only released limited data to understand SDA demand or inform market development. To understand changing housing and support approaches and the impact of NDIS housing policy on market responses, this research had three aims: (1) to examine the locations and characteristics of housing and support vacancies advertised for people with disability; (2) to investigate funding sources for, and providers of, these supported housing options; and (3) to examine the proportion and source of government, nonprofit and private sector funding for housing and support developments advertised. An audit was undertaken of all advertisements on the two main non‐government organisation Websites that list Australian supported housing vacancies. A total of 562 property adverts were reviewed in March 2019. Audit findings are considered in relation to the current NDIS policy context. Possible housing futures and market gaps for people with significant and permanent disability in Australia are discussed.